Dupilumab as a combination therapy to oral systemic immunomodulators for moderate-to-severe atopic dermatitis for skin of color children in resource-limited setting: A case series - Siti Nuraihan; M N Azmi; Sabeera Begum; Kin Fon Leong (Wolters Kluwer Medknow Publications, 2023)
Subcutaneous dupilumab, with or without topical therapy, is clinically proven to treat children with moderate-to-severe atopic dermatitis (AD). However, this well-researched biologic for AD in children is still among the most expensive medication in the world and not widely available in resource-poor areas. We share our experience managing four children with severe AD, aged 3 to 11, who poorly responded to oral systemic immunomodulators but successfully achieved rapid clinical remission when combined with subcutaneous dupilumab. No loading doses were administered to patients in this case series, and the maintenance dosages used were lower than the manufacturer's recommendations. This case series illustrates that oral immunomodulators in combination with subcutaneous dupilumab therapy are efficacious, safe, tolerable, and cost-effective for children with moderate-to-severe AD. This treatment strategy can be considered an alternative for children with AD recalcitrant to other available treatment options, especially when AD management is challenging in limited resource settings.